2018
DOI: 10.1167/iovs.17-23085
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Topical Therapies for Improving the Optical Clarity Following Stromal Wounding in a Novel Ex Vivo Canine Cornea Model

Abstract: PURPOSE. To evaluate the effect of topical suberanilohydroxamic acid (SAHA) and 5-methyl-1phenyl-2[1H]-pyridone (pirfenidone) on the degree of corneal haze in the stromal wounded ex vivo canine cornea. METHODS. Twenty-four corneoscleral rims from normal dogs were uniformly wounded with an excimer laser and placed into culture medium with an air-liquid interface. The control group (n ¼ 8) contained placebo-treated corneas. Treatment group 1 (n ¼ 8) received SAHA topically every 6 hours. Treatment group 2 (n ¼ 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 81 publications
0
26
0
Order By: Relevance
“…The closer resemblances in ocular physiology between dogs and humans can justify the integration of companion dogs into preclinical studies rather than traditional laboratory animals such as rabbits, mice and rats, as reported in the literature [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…The closer resemblances in ocular physiology between dogs and humans can justify the integration of companion dogs into preclinical studies rather than traditional laboratory animals such as rabbits, mice and rats, as reported in the literature [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…The availability of such a model presents a clear opportunity for translational research (i.e., intact innervation, tear film, blood supply), although experimentally induced corneal wounding (at risk of secondary infection) and subsequent corneal scar in dogs represent potential ethical challenges. As an alternative, other authors have established ex vivo canine corneal cultures that can be used to model wound healing and assess antifibrotic compounds, [316][317][318] or better understand the pathophysiology of herpesvirus in a virus-natural-host environment 319 ; in that study, the authors established an air-liquid canine corneal organ culture model to study acute herpetic keratitis, showing important similarities in the response to CHV-1 to what has been described for HSV-1. 319…”
Section: Corneal Injury In Dogs: In Vivo and Ex Vivo Modelsmentioning
confidence: 99%
“…Ex vivo corneal wound healing models are becoming popular in recent years, as they maintain the dynamic, complex, physiologic events of the in vivo model, while decreasing the need for live animals 19,20,22,24 . In this study, we established an ex vivo model of equine corneal wound healing while demonstrating its physiologic relevance.…”
Section: Discussionmentioning
confidence: 99%
“…The inherent challenge comes in the desire to learn more about these involved processes without either harming healthy animals in vivo or struggling with physiologic relevance and clinical applicability with in vitro models. The ex vivo corneal model has been developed in other species, 19–22 and represents a logical steppingstone between the equine in vitro ocular benchtop models and the in vivo studies, all while providing physiologically based clinically applicable conclusions 23 . Effective, species‐specific, reproducible models of corneal wound healing are of paramount importance.…”
Section: Introductionmentioning
confidence: 99%